A high‐speed tunable optoelectronic oscillator with a fine step based on semiconductor optical amplifier. Issue 2 (February 2015) - Chen, Han; Xia, Mingyu; Sun, Mingming; Sun, Xiaohan
ABSTRACT An optical tunable dual‐loop optoelectronic oscillator (OEO) based on birefringence effects in a semiconductor optical amplifier (SOA) is presented and the theoretical fundamentals of the design are explained. A prototype of the OEO with a frequency of 8.8 GHz is experimentally demonstrated. About 150 MHz tunable range at X‐band with a fine step about 15 MHz is realized by directly tuning the SOA injection current, and the tuning speed can reach to over 1 GHz/µs. The generated radiofrequency (RF) signal exhibits a good stability with a single sideband phase noise lower than −101 dBc/Hz at an offset of 10 kHz within the whole tunable range, without any narrow RF band‐pass filters in the loop. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:464–467, 2015